Doing transition as political action: Transition Network’s strategies to influence policy at the European level - Quintão, F.; Brito e Cunha, F; Fernandes-Jesus, M. (34th Society for the Advancement of Socio-Economics annual conference, 2022)
Prefigurative forms of collective action are often characterized by practices of ‘regenerative culture’, addressing social polarization, patriarchy, and the crisis of democracy (Esteves, 2020). These movements frequently seek to unravel the environment-economy dichotomy inherent in contemporary capitalism, directing their action to issues like local food systems, small-scale and alternative energy economies, sustainable communities, and housing (Star, 2020). Despite having common agendas, they present crucial differences among their discourses regarding themes such as the role of the State, degree of reform or radical innovation, degree of the imaginative character of the sustainability vision, and degree of opposition to capitalism (Feola, 2019). One of the most influential movements is the Transition Network (TN), which started with a local initiative in 2005 in Totnes, UK. Since then, it has spread to over 48 countries, and thousands of groups organized in different contexts, such as towns, villages, cities, universities, and schools. These “groups are working for a low-carbon, socially just future with resilient communities, more active participation in society, and caring culture focused on supporting each other” (Transition Network Website). The way TN deals with “the political” has been discussed differently. On the one hand, the movement has been diagnosed as post-political for not challenging pre-established power relations (Kenis, 2014). On the other hand, other scholars highlight the need for a better understanding of the complexities of the TN political strategies (Aiken, 2017) giving more attention to the meanings of “the political” addressed by the transition itself, expressed by actors involved in these initiatives (Lebrun-Paré, 2018). Therefore, this work aims to analyse how TN: mobilize, frame and communicate the policy claims of CLIs at regional, national, and European Union levels; position themselves in the political debate; participate (influence and are influenced) in relevant public policies; are recognized as political actors; transpose responses from public institutions to grassroots level; and how external/internal pressures influence its political strategy. This research will combine textual and archival investigation as well as participant observation and in-depth interviews. Textual and archival research will cover a range of documents produced and/or deployed by the transition network. Interviews will involve key actors identified through archival research and snowball sampling. By mapping, comparing, and contrasting processes of institutional communication, relationship-building, and policy advocacy, this paper will discuss in the end the TN’s political strategy embedded in a political, social, economical, and cultural environment.